1988
DOI: 10.1128/iai.56.10.2563-2569.1988
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous tumor necrosis factor (cachectin) is essential to host resistance against Listeria monocytogenes infection

Abstract: During a sublethal murine infection with Listerid monocytogenes cells, tumor necrosis factor (TNF) activity was detectable in neither sera nor spleen homogenates at any stage of the infection when a bioassay with L-929 cells (<4 U/ml) was used. However, injecting the mice with an immunoglobulin fraction obtained from a rabbit hyperimmunized with recombinant murine TNF-a resulted in acceleration of listeriosis. When 1 mg of anti-TNF antibody was injected per mouse, all the mice died from listeriosis, even thoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
146
0
1

Year Published

1990
1990
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 316 publications
(151 citation statements)
references
References 39 publications
4
146
0
1
Order By: Relevance
“…The in vitro incubation of BRM-induced effectors with cytokines such as IFNy, TNFa and IL-2, known to activate microbicidal activity of macrophages and PMN in other experimental systems [16,48,49], did not induce anti-GBS-090 activity.…”
Section: Discussionmentioning
confidence: 90%
“…The in vitro incubation of BRM-induced effectors with cytokines such as IFNy, TNFa and IL-2, known to activate microbicidal activity of macrophages and PMN in other experimental systems [16,48,49], did not induce anti-GBS-090 activity.…”
Section: Discussionmentioning
confidence: 90%
“…A number ofother cytokines such as TNF and GM-CSF can also induce killing of Listeria, leishmania, and trypanozome by macrophages [25][26][27][28][29]. It is not known if RNI are also involved in cytotoxicity induced by cytokines other than IFN-y.…”
Section: Discussionmentioning
confidence: 99%
“…Although LPS triggers TNF release from murine peritoneal macrophages in vitro [22.23], no TNF-a was detected in peritoneal exudate or blood from animals of either strain during the first 24 h of a BT-induced inflammatory response. Nakane et al [24] reported comparable findings in Z. (.s7er/o-inrected mice where, despite the fact that no TNF-a was detected (L929 bioassay, <4/i/tnl) in serum or spleen homogenates at any time point, injection of animals with anti-TNF-rv antibody 0-2 h p.i.…”
Section: Discussionmentioning
confidence: 69%